Management of a Patient with a Thoracic Epidural After Accidental Clopidogrel Administration. (15th July 2015) - Hah, Jennifer M.; Noon, Kristen; Gowda, Abhishek; Brun, Carlos
Abstract : We report a case of accidental clopidogrel administration in a patient receiving ongoing epidural analgesia postoperatively. The epidural catheter was removed 7 hours after the clopidogrel dose without incident. The onset of inhibition of adenosine diphosphate−induced platelet aggregation in healthy individuals has been reported at 12 to 24 hours after administration of a single 75-mg dose of clopidogrel. This case demonstrates the importance of understanding clopidogrel's pharmacology to avoid ordering unnecessary tests, which may delay catheter removal. Consideration of appropriate testing and limitations in the context of unintentional antiplatelet administration with indwelling neuraxial catheters is discussed.